Teacher–Parent Collaboration as an Educational Da'wah Communication Strategy in Mitigating the Influence of Western Popular Culture on Early Childhood Development - Irma Suriani; Mutmain Natulaila Noviana; Baiq Ulfa Azizah; Siti Hawa; Khoirurrozikin (Journal of Education, Teaching, and Learning, 2026)
The rapid expansion of globalization, digital technology, and transnational media has intensified young children's exposure to Western popular culture, creating challenges for the preservation of religious values, moral development, and cultural identity. This study aims to analyze the conceptual construction of teacher–parent collaboration from the perspective of educational da'wah communication, examine the forms, impacts, and challenges of Western popular culture on early childhood development, and explore educational da'wah communication strategies for mitigating these influences. This study employed a qualitative literature review design. Data were collected from scholarly publications indexed in reputable academic databases, including Scopus, Web of Science, ERIC, SpringerLink, Taylor & Francis, ScienceDirect, and Google Scholar. The selected literature consisted of publications published between 2021 and 2026 focusing on teacher–parent collaboration, educational communication, educational da'wah, digital literacy, popular culture, and early childhood education. Data were analyzed using thematic content analysis to identify recurring themes, conceptual relationships, and research gaps. The findings reveal that teacher–parent collaboration functions as a strategic educational partnership that strengthens value transmission, character formation, and religious identity through educational da'wah communication. Western popular culture influences children through digital media, entertainment platforms, consumer culture, and language practices, producing both developmental opportunities and moral, cultural, and behavioral challenges. Effective mitigation strategies include continuous family–school communication, Islamic character education, parental mediation of digital media use, and collaborative value alignment among families, schools, and communities. The study concludes that educational da'wah communication provides a comprehensive framework for strengthening children's cultural resilience, enabling them to engage constructively with global cultural influences while maintaining their religious values, moral character, and cultural identity.